Secret sharing scheme for collaborative access system - Kadir, Rashidah; Maarof, Mohd. Aizaini (2000)
This research investigate the concept of secret sharing scheme based on Shamir's secret sharing. The goal of this research is to implement secret sharing scheme for collaborative access system which are ideally suited to application in which a group of mutually suspicious individuals with conflicting interest must cooperate. In (q,n) secret sharing, a quorum, q of a group of n users are allowed to access the system by having the quorum reconstruct a secret(key), less than quorum can gain no information. Lost or stolen share still ensure the security of resources.